Environmental Cost Management Accounting in Fdi Enterprises - Anh, Nguyen Tuan (Business and Economic Research, 2024)
Environmental management accounting was established in developed countries around the world in the 1970s. In Vietnam, environmental management accounting has also gradually formed and developed. Through a survey of 200 FDI enterprises of various sizes and industries, but with a common point of strong impact on the environment, the author found that businesses have not yet truly applied environmental cost management accounting in their production and business processes. Therefore, the author proposes some solutions to apply environmental cost management accounting in Vietnam's FDI enterprises.